Book Reader using Raspberry Pi - Sabin Prasanna, P; Bernadine Infenta, B; Maria Keerthana, S; Sophie Maria Vincent, Sherril (International Journal of Computer Sciences and Engineering, 2025)
Image-based sequence recognition has been a long-standing research topic in the field of computer science and technology. This project focuses on investigating the problem of text recognition, which is among the most important and challenging tasks in image-based sequence recognition. It mainly focuses on effects of uniform and full height map correction methods for dwarfing book spread images in an automated book reader design for individuals with visual impairment and blindness. The accuracy of the book spread images is quantified and measured by introducing the corrected images to an Optical Character Recognition engine. Based on character recongnization algorithm one can achieve the text to speech conversion and accuracy of speech is more. Camera-based assistive text reading framework and audio output along with Raspberry Pi is used in this project. Robotic assistive based page rotation is used to turn the pages of the book. It is working based on deep learning system especially applied to address the challenging process of book digitization.